The air engine stirling cycle for a sustainable future - Organ, Allan J. (CRC Press Boca Raton, 2007)
Two centuries after its original invention, the Stirling engine has finally emerged as a commercial reality. Providing an alternative to centralized power generation, the Stirling is now employed as the core component in domestic CHP (combined heat and power) technology, which offers substantial savings in raw energy utilization and in doing so also addresses current concerns regarding hydrocarbon consumption and greenhouse gas emissions. The successful use of the Stirling requires the addressing of a range of issues, including the long-standing mismatch between inherently favorable internal efficiency and wasteful external heating provision; the dearth of data on heat transfer and flow related to the task of first-principles design; and its limited RPM capability when operating with air (and nitrogen) as working fluids. All of these matters are explored in depth in The Air Engine: Stirling Cycle Power for a Sustainable Future. The account also includes previously unpublished insights into the character and potential deployment of two related engines -- the pressure-wave and thermal-lag.
Keywords: Engine -- Air; Stirling engines